Answer:
Step-by-step explanation:
Answer:
<h2>
(A.C.) 54 - 36 = m</h2>
Step-by-step explanation:
36 + m = 54 <em>subtract 36 from both sides</em>
36 - 36 + m = 54 - 36
m = 54 - 36
m = 18
First subtract 4 from both sides
![13 - 4 - 5m = - 6m](https://tex.z-dn.net/?f=13%20-%204%20-%205m%20%3D%20-%206m)
then simplify
![9 - 5m = - 6m](https://tex.z-dn.net/?f=9%20-%205m%20%3D%20-%206m)
add -5 to both sides
![9 = - m](https://tex.z-dn.net/?f=9%20%3D%20-%20m)
since a variable shouldn't be negative the answer should be
![m = - 9](https://tex.z-dn.net/?f=m%20%3D%20-%209)
(I prefer having the variable on the left side)
Answer:
step back u idiot
Step-by-step explanation: